The queen of nothing - Black, Holly (Black, Holly. Folk of the Air, 2019)
Jude, the exiled mortal Queen of Faerie, is in the human world but is forced back to the Faerie High Court to save her sister, Taryn. And once in an Elfhame she doesn't recognize, she is also once again forced to confront her feelings for Cardan. Jude feels a war brewing and she must find a way to break a dark curse.